New hosts of Myrothecium spp. in Brazil and a preliminary in vitro assay of fungicides - Quezado Duval, A.M. (2010)
Myrothecium roridum and M. verrucaria are two plant pathogenic species causing foliar spots in a large number of cultivated plants. This paper aims to study the causal agents of foliar spots in vegetable crops (sweet pepper, tomato and cucumber), ornamental plants (Spathiphyllum wallisii, Solidago canadensis, Anthurium andreanum, Dieffenbachia amoena) and a solanaceous weed plant (Nicandra physaloides). Most of the isolates were identified as M. roridum; only the isolate 'Myr-02' from S. canadensis was identified as M. verrucaria. All the isolates were pathogenic to their original plant hosts and also to some other plants. Some fungicides were tested in vitro against an isolate of M. roridum and the mycelial growth recorded after seven days. Fungicides with quartenary ammonium, tebuconazole and copper were highly effective in inhibiting the mycelial growth of M. roridum. This paper confirms the first record of M. roridum causing leaf spots in sweet pepper, tomato, Spathiphyllum, Anthurium, Dieffenbachia and N. physaloides in Brazil. We also report M. roridum as causal agent of cucumber fruit rot and M. verrucaria as a pathogen of tango plants.